Função do diretor na escola pública paulista: mudanças e permanências - Abdian, Graziela Zambão [UNESP]; Oliveira, Maria Eliza Nogueira [UNESP]; Jesus, Graziela De [UNESP] (Universidade Federal do Rio Grande do Sul (UFRGS), Faculdade de Educação, 2013)
This essay is intended for an analysis of the principal's duties in São Paulo State school, considering the conceptions of Administration specialists, Education professionals and the legal directives pertinent to the State government. It was interesting the procedures of rereading and analyzing of the literature of the area; the survey and analysis of legal documents which, direct or indirectly, concern the principal's duty and the accomplishment, transcription and analysis of half elaborated interviews with administrators and teachers. At the end of this research, it was found some contradictions in the conception of School Administration like it is diffused in different contexts, which anyway reflects the conceptions of the respondents.

Com este estudo, pretende-se analisar a função do diretor na escola estadual paulista, à luz das concepções dos especialistas da Administração Escolar, da percepção dos profissionais da Educação e das diretrizes legais pertinentes ao governo estadual. Neste contexto, interessam os procedimentos de releitura e análise da literatura da área; o levantamento e análise de documentos legais que, direta ou indiretamente, referem-se à função do diretor de escola e a realização, transcrição e análise de entrevistas semielaboradas com gestores e equipes de docentes. Os resultados da análise indicam contradições na percepção da Administração Escolar, tal como difusa nos diferentes âmbitos que, de certa forma, refletem-se nas concepções dos entrevistados.
The duties of the principal in são paulo state schools: changes and continuities
Keywords: Diretor de Escola; Política Educacional; Organização do Trabalho na Escola; Principal's Duties; Educational Policy; Organization of Working as School